2022
DOI: 10.1037/met0000393
|View full text |Cite
|
Sign up to set email alerts
|

Using structural equation modeling to study traits and states in intensive longitudinal data.

Abstract: We wish to thank prof. dr. Peter de Jonge and the team of HoeGekisNL, as well as the participants, for allowing us to use their data in this study. We would also like to thank the Center for Information Technology of the University of Groningen for their support and for providing access to the Peregrine high performance computing cluster.Partial results of this study were presented at the measurement error in longitudinal data workshop held in the university of Manchester in June 2019 and at the IMPS 2019 meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 88 publications
(264 reference statements)
0
20
0
Order By: Relevance
“…The ME-TSO model presented in this study aims to be an additional tool to model psychological dynamics. The model integrates the multilevel TSO (Castro-Alvarez et al, 2021), the LST-RF approach (Geiser et al, 2015), and the DSEM framework (Asparouhov et al, 2018). In general, the ME-TSO model allows studying the carry-over effects of psychological constructs, the person-situation interaction effects, and the psychometric properties of the items per individual across fixed situations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ME-TSO model presented in this study aims to be an additional tool to model psychological dynamics. The model integrates the multilevel TSO (Castro-Alvarez et al, 2021), the LST-RF approach (Geiser et al, 2015), and the DSEM framework (Asparouhov et al, 2018). In general, the ME-TSO model allows studying the carry-over effects of psychological constructs, the person-situation interaction effects, and the psychometric properties of the items per individual across fixed situations.…”
Section: Discussionmentioning
confidence: 99%
“…This means that it has been presented as a single-level model, which requires the data to be in wide format (i.e., one row per subject and one column for each repeated measure). However, we have previously presented a multilevel version of the TSO model (Castro-Alvarez et al, 2021), the path diagram of which is shown in Figure 1. In contrast to the single-level TSO model, the multilevel TSO model requires the data in long format and is therefore more suitable to analyze intensive longitudinal data.…”
Section: The Trait-state-occasion Modelmentioning
confidence: 99%
See 3 more Smart Citations